THE RELATIONSHIP BETWEEN TEACHER'S PERCEPTION OF SCHOOL CLIMATE AND THEIR JOB SATISFACTION AT EXPERIMENTAL MIDDLE SCHOOL, ZHONGSHAN CITY, GUANGDONG, CHINA - ZHENG, YUHANG; YE, YAN (Scholar: Human Sciences, 2022)
In this research, the research instruments used were the Organizational Climate Index (OCI) designed by Hoy, Smith, and Sweetland (2002) based on the Open and Closed School Climate and the Healthy School Climate Theory, and the Organizational Climate Index (OCT) to determine teachers' perception of the school climate, which initially designed by Hoy et al. (2002). The collected data was analyzed by Descriptive statistics, Frequency and Percentage, Mean and Standard Deviation, and Pearson Product Moment Correction Coefficient. Researchers collected basic information from 56 teachers at the selected school, including teaching experience, year, age, and educational level. The research findings showed the level of the teachers' perceptions of the school climate was high(3.60), while the level of the teachers' job satisfaction at this Middle School was high(3.62). The correlation analysis result showed a strong positive relationship between teachers' perceptions of the principal's transformational leadership style and their job satisfaction at Experimental Middle school in Zhongshan City, China.